Strengthening Moslem Society’s In New Media To Improving Tolerance and Pluralism In Indonesia - Basit, Abdul; Muyasaroh, Hanifah; Nawawi; Ahmad, Shakila (Advances in Humanities and Contemporary Studies, 2024)
There are three studies in this research, namely the study of new media, encouraging the participation of the Moslem society in new media and promoting tolerance and pluralism through new media. This study is important considering that Indonesia is a pluralistic nation consisting of various tribes, nations, religions and beliefs, so that social and religious friction and conflict are very easy to happen. According to the Komnas HAM report for the 2020 period, there were 23 reports of violations of houses of worship in various regions of Indonesia and cases of massacres of Church congregations, Bala Keselamatan, Sigi Regency, Central Sulawesi followed by the burning of Church service posts. The cases are the background of the importance of promoting tolerance and pluralism in Indonesia. The society of Indonesia need to be encouraged to participate actively by conveying their ideas, opinions and thoughts on social media so that the values of tolerance and pluralism can be fostered. The theory used is community participation. This research is qualitative research using a library research approach. The results of this research; first, encouraging the continuous use of social media such as blogs, Facebook and Twitter as a new form of community participation in conveying ideas and thoughts about tolerance and pluralism. For example, the Instagram accounts @nugarislucu, @katholic_garis_lucu,@muhammadiyahgl,@buddhisgl,@protesgarislucu. Second, point is to provide rewards (reinforcement), namely users can provide positive comments, likes, or subscribe. With this response, users feel appreciated so they will repeat it again.